FAKTOR YANG MEMPENGARUHI TERJADINYA KONTAK POSITIF DIFTERI DI KABUPATEN JEMBER - Wahjudi, Pudjo; Setyowati, Nining (FKM - UNEJ, 2011)
Diphtheria is a reemerging disease. In Jember Regency, diphtheria cases have increased from the year 2009 with 2 cases and 2010 up to 6 cases. Positive contact of diphtheria is a potential source of infection. The objective of this research was to analyze the factors that influence the positive contacts of diphtheria. This research used cross sectional design. This research was conducted in 6 working areas of public health centers in Jember Regency. Subjects were all positive and negative contact cases based on the laboratory results in 2010Â from Jember District Health Office. The sampling techniques used were proportional random sampling. The samples involved were 61 people. Data analysis used was logistic regression test with Î± = 0.05. The research results showed that the significant factors influencing the occurrence of positive contacts of diphtheria were age (0.042) and the closeness of contacts (0.001). Meanwhile, the factors that mostly affected the occurrence of positive contacts of diphtheria were the closeness of contacts with the risk of 12.4 times higher in one-home close contacts than those in neighborhood, school friends and playmates. The recommendations that can be given are to provide prophylaxis on all contacts of diphtheria, to use a mask at the positive contacts of diphtheria, to employ a drug-taking supervisor in the delivery of prophylactic medication, to provide additional immunization of diphtheria toxoids to the age of adolescence and adulthood, and to socialize health-record card keeping ââ. Key words: diphtheria, positive contacts